Papel da via WNT no desenvolvimento de células B-1 - Osugui, Lika [UNIFESP] (2016)
Hematopoietic stem cells (HSC) are capable to generate multipotent progenitors that produce all blood cell lineages, and exhibit high proliferative potential and are able to self-renewal. Several molecules has been described to participate in the embryo cells development and commitment. In this context, Wnt proteins have an important role in many biological processes, included participation in different stages of the lymphocyte development and HSC self-renewal. Although B-1 cells are considered mature cells, they express two different programs simultaneously, the lymphoid and myeloid ones, and are self-renewing cells. In order to evaluate the role that Wnt pathway plays in this permissiveness and the self-renewal property, B-1 cells were purified and the Wnt receptors expression were verified by qPCR, showing the Fzd6 are the most expressed Wnt receptor. In co-culture experiments of B-1 and OP9 cells, stimulated or not with Wnt3a or Wnt5a, increased amount of viable and proliferative cells were observed in the Wnt3a treated group. The canonical Wnt signaling activation was assessed by Axin2 expression that was detected in the both treated groups. When the transcription factors related to lymphoid and myeloid lineage were analyzed, the Flt3 gene was upregulated after the both stimuli and IL- 7R was upregulated only when Wnt3a was added to the cultures. Despite of in vitro results indicated the role of canonical Wnt signaling in the B-1 self-renewal, the in vivo assays involving adoptive Wnt-reporter mice (Axin2+/lacZ) derived-B-1 cell transference to RAG-1 mice did not demonstrate increase number of the Wnt activated B-1 cells. Interestingly, B-1 progenitors (B-1P) showed an expressive response when cultivated onto Wnt5a-transduced OP9 cells, expanding their pool 40 times more in relation to the input cell number. Moreover, in the presence of Wnt3a- transduced OP9 cells, B-1P originated a significant population of CD5+ cells. Altogether, these data suggest that mature B-1 cells, and mainly B-1 progenitors are able to respond to Wnt ligands and this signaling could be important to maintenance of this B cell subtype. The pronounced response to Wnt ligands observed in the progenitors suggests that this Wnt pathway could be involved in the B-1 cell development and differentiation process.